2004
DOI: 10.1186/1477-7827-2-83
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Retinoids are recognized as important regulators of vertebrate development, cell differentiation, and tissue function. Previous studies, performed both in vivo and in vitro, indicate that retinoids influence several reproductive events, including follicular development, oocyte maturation and early embryonic development. The present study evaluated in vitro effects of retinol addition to media containing maturing bovine oocytes and developing embryos in both a low oxygen atmosphere (7%) and under atmospheric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 40 publications
0
15
1
Order By: Relevance
“…Moreover, the number of cells per blastocyst was not influenced by any of the ROH treatments. These results are in disagreement with those obtained in bovine IVF, where it has been reported that 5000 nm ROH during IVM increases embryonic development to the blastocyst stage (Livingston et al 2004). It may be that different concentrations of ROH to those used in the present study are required during porcine IVM to achieve improved embryo development.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Moreover, the number of cells per blastocyst was not influenced by any of the ROH treatments. These results are in disagreement with those obtained in bovine IVF, where it has been reported that 5000 nm ROH during IVM increases embryonic development to the blastocyst stage (Livingston et al 2004). It may be that different concentrations of ROH to those used in the present study are required during porcine IVM to achieve improved embryo development.…”
Section: Discussioncontrasting
confidence: 97%
“…This detrimental effect could be related to a retinoid imbalance that has been shown to be highly correlated with developmental abnormalities (Morriss-Kay and Ward 1999). In support of this hypothesis, high concentrations of retinoids during IVM, such as 500 nm RA and 100 µm ROH (Livingston et al 2004), have been shown to be detrimental for bovine oocytes. In contrast with these findings, Lima et al (2006) reported that the addition of 500 nm RA to bovine IVM medium enhanced blastocyst formation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Duque et al [8] showed that the cytoplasmic competence of bovine oocytes improved in the presence of cis-retinoic acid during prematuration. Moreover, Livingston et al [13] demonstrated that the addition of retinol to the IVM medium may improve the embryonic development and blastocyst rate of bovine oocytes.…”
Section: Introductionmentioning
confidence: 99%